1991
DOI: 10.1002/j.1460-2075.1991.tb04900.x
|View full text |Cite
|
Sign up to set email alerts
|

A factor that positively regulates cell division by activating transcription of the major cluster of essential cell division genes of Escherichia coli.

Abstract: Cell division in Escherichia coli requires the products of the ftsQ, ftsA and ftsZ genes. It is not known how the cell regulates the cellular concentrations of these essential elements of the division system. We describe here a factor that activates cell division by specifically increasing transcription from one of the two promoters that lie immediately upstream of the ftsQAZ gene cluster. The trans‐acting factor is the product of the sdiA gene, which was isolated on the basis of its ability to suppress the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
193
2
3

Year Published

1993
1993
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 199 publications
(206 citation statements)
references
References 44 publications
8
193
2
3
Order By: Relevance
“…The doublet RNase E cleavage site responsible for the 'pZ1' RNA species represents only 6%. Other estimates of the relative strength of these promoters, based on studies with transcriptional fusions (Yi et al, 1985;Wang et al, 1991;Flä rdh et al, 1997), found about 60% of the total ftsZ mRNA species started from pZ4-pZ3-pZ2-'pZ1', compared with 92% in our study (Table 4). However, the strength of several of these promoters has been shown to vary considerably with growth rate and with growth phase (Dewar et al, 1989;Aldea et al, 1990;Robin et al, 1990;García-Lara et al, 1996;Flärdh et al, 1997).…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…The doublet RNase E cleavage site responsible for the 'pZ1' RNA species represents only 6%. Other estimates of the relative strength of these promoters, based on studies with transcriptional fusions (Yi et al, 1985;Wang et al, 1991;Flä rdh et al, 1997), found about 60% of the total ftsZ mRNA species started from pZ4-pZ3-pZ2-'pZ1', compared with 92% in our study (Table 4). However, the strength of several of these promoters has been shown to vary considerably with growth rate and with growth phase (Dewar et al, 1989;Aldea et al, 1990;Robin et al, 1990;García-Lara et al, 1996;Flärdh et al, 1997).…”
Section: Discussioncontrasting
confidence: 56%
“…When FtsZ is in moderate excess, polar septa are formed, giving rise to minicells Garrido et al, 1993). Moderate overproduction of FtsZ relieves the division inhibition caused by high levels of the division inhibitor SulA (Lutkenhaus et al, 1986), the division inhibitor MinCD (Bi and Lutkenhaus, 1990;Wang et al, 1991) or the trigger factor (Guthrie and Wickner, 1990), as well as that observed in the absence of the molecular chaperone DnaK (Bukau and Walker, 1989). At high FtsZ concentrations, cell division is completely blocked .…”
Section: Introductionmentioning
confidence: 99%
“…The ftsQAZ gene cluster is regulated by multiple promoters, with the P, and P2 promoters being upstream of the ftsQA genes (24,25). It has been shown that only the P2 promoter is affected by SdiA overexpression (13). Here we show that transcription from the SdiA-regulated P2 promoter satisfies all three requirements of an autoinduction system, suggesting that an autoinduction mechanism is involved in regulation of these genes.…”
mentioning
confidence: 49%
“…The SdiA protein from E. coli has an amino acid sequence similar to that of LuxR and has been proposed to activate transcription of the ftsQAZ gene cluster, which is required for cell division (13). The homology between LuxR and SdiA suggested to us the possibility that SdiA might function by a mechanism similar to that of LuxR.…”
mentioning
confidence: 98%
See 1 more Smart Citation